Development of a microfluidic tool for understanding whole cell algal cultures - Glover, K (2014)
This project focuses on the development, characterisation and use of a microfluidic tool to study cells in suspension, and the motility of cells. This microfluidic tool is designed to have a low convective flow, so transport is dominated by diffusion, which allows a 2D concentration gradient to be maintained and manipulated, and cells to swim without advection. The rheology of the whole cell cultures was measured and found to shear thinning. Bubbles rising through the fluid was modelled. Despite this, it was found that bubbles rising through whole cell culture would impose a shear that correlated to the viscosity at the high shear plateau. That is bubble size did not significantly affect the apparent viscosity. The medium around bubbles of any size, from 1 mm to 100 mm, has a viscosity of 0.001 Pas. Numerical simulations are used to characterise and optimise the design and operation of the microfluidic devices. Low advection within the central chamber, with desired concentration gradients, was attainable with provided the geometry and operation were within certain limits. Recommendations regarding the geometry of the device include an inlet width to inlet neck length ratio of less than 2 and a radius of less then 400 um. The inlet velocity controlled the maximum velocity within the chamber. PDMS devices were fabricated and operated and it was found that concentration gradients could be maintained, but there were limitation regarding the syringe pump. Proof of concept is presented for visualising cells within this microfluidic device. From this thesis, it has been shown that microfluidic devices have important potential for understanding the motility of microalgae in real environments and in controlled concentration gradients, although they require careful analysis and thoughtful fabrication.